2015
DOI: 10.1021/acs.orglett.5b02464
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Aza-Diketopiperazines Enabled by Controlled Reactivity of N-Isocyanate Precursors

Abstract: A one-pot sequence for the synthesis of aza-diketopiperazines is reported, involving carbazate acylation with chloroacetyl chloride, SN2 with a primary amine, N-isocyanate formation, and cyclization. Nitrogen-substituted isocyanates (N-isocyanates) are a rare class of amphoteric isocyanate with high, but severely underdeveloped synthetic potential. This approach highlights that βN-acyl carbazates can act as blocked (masked) N-isocyanates, thus allowing a challenging intermolecular SN2 reaction of a primary ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Indeed, cyclization using the proximal nitrogen (αN) would yield the 5-membered amino-hydantoin, while cyclization using the distal nitrogen (βN) would yield the 6-membered aza-diketopiperazine. 13 We tested the reaction with a proline ester, and were pleased to observe complete selectivity for amino-hydantoin formation (eqn (3)). 12 After this initial result, we decided to further explore this reactivity using N -benzyl carbazate and several amino-esters ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, cyclization using the proximal nitrogen (αN) would yield the 5-membered amino-hydantoin, while cyclization using the distal nitrogen (βN) would yield the 6-membered aza-diketopiperazine. 13 We tested the reaction with a proline ester, and were pleased to observe complete selectivity for amino-hydantoin formation (eqn (3)). 12 After this initial result, we decided to further explore this reactivity using N -benzyl carbazate and several amino-esters ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the above experimental results together with related reports, a possible mechanism for the reaction is proposed (Scheme ). Initially, Rh(PPh 3 ) 3 Cl undergoes an insertion reaction with α‐diazocarbonyl compound L1 to give Rh‐carbene A .…”
Section: Resultsmentioning
confidence: 65%
“…Intermediate B is oxidized by O 2 (from air), and this is followed by homolysis of the O–O bond to give intermediate E . Finally, intermediate E reacts with alcohols or amines to give the desired products 2 or 3 (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…In similar fashion, a focus on original 1,2,5‐oxadiazine‐3,6‐diones (1,2,5‐Oxd), which can be considered as oxa‐diketopiperazines (oxa‐DKPs) is presented here. While aza‐DKPs were recently studied, synthetic access to oxa‐DKPs is poorly described. Geffken et al.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In similar fashion, a focus on original 1,2,5-oxadiazine-3,6-diones (1,2,, which can be considered as oxa-diketopiperazines (oxa-DKPs) is presented here. While aza-DKPs were recently studied, [7] synthetic access to oxa-DKPs is poorly described. Geffken et al briefly reported the double addition of N,Ndialkylhydroxamic amino acids on carbonyldiimidazole afford-ing a poorly functionnalized collection of oxa-DKPs in good yields (Scheme 1, a).…”
Section: Introductionmentioning
confidence: 99%